Bukhta Nagaeva (Volok) Po menzulʹnoĭ sʺemki︠e︡ Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okena 1912 g. / Sʺemka i chernīe Podpolkovnika Velʹiozhnago; Kopiroval Kap. mal. pl. Mat︠s︡evich; Tipo-litografīi︠a︡ Īosif Korotʹ. Vladivostok. - Russia. Glavnoe gidrograficheskoe upravlenīe; (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1912)
Relief shown by form lines and spot heights. Depths shown by soundings and isolines.; Title translation: Nagaev Bay (Volok), according to the survey of the Hydrographic Expedition of the Pacific Ocean 1912.; "Masshtabʺ 1/42000 (1 v. vʺ di︠u︡ĭmi︠e︡)" = Scale 1/42000 (1 verst in 1 inch).; "Astronomicheskīi punkti︠e︡ i sklonenīe kompasa opredi︠e︡leny Generalʺ-Maīoromʺ Zhdanko vʺ 1912 g." = Astronomical points and compass declination were determined by Major-General Zhdanko in 1912.; "218" -- lower right margin Grayscale; 1:42,000